2022
DOI: 10.1039/d2dt01357f
|View full text |Cite
|
Sign up to set email alerts
|

Coordination mode and stability of the tetrahydroborate ligand in group 10 metal pincer complexes

Abstract: The coordination mode of the BH4- ligand in transition metal tetrahydroborate complexes is mainly dominated by the nature of the metal centres. However, other factors can also play important roles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It is likely that the corresponding tetrahydroborate complex forms first in the reaction, which decomposes under the reflux condition to generate the hydride complex 1a . This is very common for pincer ligated transition-metal tetrahydroborate complexes . Complex 1a was fully characterized by multinuclear NMR, FTIR, crystallography analysis, HRMS, and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the corresponding tetrahydroborate complex forms first in the reaction, which decomposes under the reflux condition to generate the hydride complex 1a . This is very common for pincer ligated transition-metal tetrahydroborate complexes . Complex 1a was fully characterized by multinuclear NMR, FTIR, crystallography analysis, HRMS, and elemental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The CS double bond in carbon disulfide can insert into most transition metal hydride bonds to form dithioformato complexes. , The coordination mode of the dithioformato ligand in the resulting insertion products can be either κ 1 - S -S 2 CH or κ 2 - S,S′ -S 2 CH depending on the nature of the metal center. We wondered whether there is any difference between 1a and 2a when they are reacted with carbon disulfide and how the PNCNP and POCOP pincer backbones influence the dithioformato auxiliary ligand in the resulting products.…”
Section: Resultsmentioning
confidence: 99%
“…The metal center in a pincer complex is effectively chelated by the pincer ligand, and the rigid pincer backbone can rarely be influenced by other auxiliary ligands. On the other hand, the structure and property of the auxiliary ligands can be significantly affected by the pincer platforms. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were interested in the structure, reactivity and catalytic applications of transition metal complexes supported by different types of pincer platforms. 6,14 The unique structural features of the PNCNP pincer platform encouraged us to initiate a study of the reactivity and catalytic applications of palladium( ii ) complexes supported by a benzene-based PNCNP pincer platform. We found that the hydride complex [2,6-( t Bu 2 PNH) 2 C 6 H 3 ]PdH ( 1 ) has very strong deprotonating ability and versatile catalytic activity; and the pincer backbone also exhibits good water stability.…”
Section: Introductionmentioning
confidence: 99%